2015
DOI: 10.5330/1096-2409-19.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing School Counselors’ Suspecting and Reporting of Childhood Physical Abuse: Investigating Child, Parent, School, and Abuse Characteristics

Abstract: This study sought to explore possible child abuse reporting disparities among school counselors. The participants in this study were elementary school counselors (N = 398) from across the United States. Each participant read a series of vignettes and completed a survey regarding their inclinations about suspecting and reporting childhood physical abuse. The surveys manipulated the following variables: student race, family socioeconomic status (between-subject variables), relationship with the school counselor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Examples include “because of the decision to use e‐mail and instant messenger for data collection, the researchers could not obtain additional information from students’ nonverbal or verbal behavior” (Henfield, Woo, & Washington, 2013, p. 134); “E‐mail data collection seemed to elicit more brief responses; phone interviews, while no prompting was offered, elicited richer responses with more details” (Dollarhide, Smith, & Lemberger, 2007, p. 367); and “since the survey was administered online, the researchers had no control over the environment in which the survey was taken. Discerning whether or not the environment could have had an effect on participant responses is difficult” (Tillman et al, 2016, p. 112). Of the 10 times this code was noted in the articles we reviewed, four of the articles were relating the issue specifically to qualitative data, whereas the remaining six articles were related to quantitative data.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include “because of the decision to use e‐mail and instant messenger for data collection, the researchers could not obtain additional information from students’ nonverbal or verbal behavior” (Henfield, Woo, & Washington, 2013, p. 134); “E‐mail data collection seemed to elicit more brief responses; phone interviews, while no prompting was offered, elicited richer responses with more details” (Dollarhide, Smith, & Lemberger, 2007, p. 367); and “since the survey was administered online, the researchers had no control over the environment in which the survey was taken. Discerning whether or not the environment could have had an effect on participant responses is difficult” (Tillman et al, 2016, p. 112). Of the 10 times this code was noted in the articles we reviewed, four of the articles were relating the issue specifically to qualitative data, whereas the remaining six articles were related to quantitative data.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the vignette mean scores of school counselors who would report abuse was higher than the mean score of school counselors who suspected abuse (Tillman et al, 2015). These results suggested that school counselors are more likely to report even if suspicion is low (Tillman et al, 2015). However, responding to a vignette does not mean that school counselors would respond in a similar way if presented with a situation in person.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Regarding training experiences, Tillman et al (2015) conducted a survey asking 398 practicing school counselors from across the United States to respond to one of six different vignettes of child maltreatment with a different race, socioeconomic status, and severity of abuse. They found that the vignette mean scores of school counselors who would report abuse was higher than the mean score of school counselors who suspected abuse (Tillman et al, 2015). These results suggested that school counselors are more likely to report even if suspicion is low (Tillman et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, victims do not receive specialized help and support [19,24] or do not disclose their experiences [25]. Many reasons for this behavior have been described by previous studies, such as low levels of knowledge or poor training, fear of the consequences for the victim, the family, the reporter and the school or lack of support from the school management team [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%